Play pricking - Anicca, Abhishek (Research and Humanities in Medical Education, 2021)
This is a poem I wrote in the hospital while recovering from COVID this year. It is always difficult for people to find my veins for inserting an IV and it always turns into a theater of the absurd. This poem talks about that experience in the hope that it also reflects how, everyday, all of us are play pricking, trying to find the veins of our life.